Kualitas Fisik Silase Rumput Gajah dan Ampas Tahu Segar dengan Penambahan Sirup Komersial Afkir: The Physical Quality of Elephant Grass and Fresh Tofu Dregs Silage with Rejected Commercial Syrup Addition (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
This study aimed to evaluate the addition of rejected commercial syrup on the physical quality of silage made from elephant grass and fresh tofu dregs. The making process and harvesting of silage were conducted out at the Laboratory of Nutrition and Feed Technology, Faculty of Agriculture and Animal Husbandry, UIN Suska Riau. The ingredients used were elephant grass, fresh tofu dregs, and commercial syrup. Completely Randomized Design (CRD) consisting of 3 treatments and 7 replications was used in this study. The treatments in this study were P1: elephant grass + fresh tofu dregs, P2: P1 + 5% commercial syrup, and P3: P1 + 10% commercial syrup. Variable observed were dry matter loss, temperature, pH, color, texture, aroma, and fungal growth. The data obtained were analyzed based on analysis of variance, and if there was a significant effect between treatments, then it was followed by Duncan's test at 5% level. The results of this study that the addition of rejected commercial syrup had a significant effect (p